PERBANDINGAN MODEL INKUIRI DAN PROBLEM-BASED LEARNING DALAM PEMBELAJARAN IPA: SYSTEMATIC LITERATURE REVIEW META-ANALIS - Mahrelin, Mahrelin; Nurul Hidayah; Yatin Mulyono (Jurnal Metabio, 2025)
This study aims to analyze and compare the effectiveness of the Inquiry and Problem-Based Learning (PBL) models in science education through a systematic literature review and meta-analysis approach. The study examines various scientific publications that meet inclusion criteria based on research design, topic relevance, and completeness of quantitative data. Collected data were analyzed to identify trends in the effectiveness of both models in enhancing students’ science process skills and critical thinking abilities. Meta-analysis was conducted on selected articles with complete statistical data to calculate effect sizes as indicators of the strength of influence. The results indicate that both instructional models show high effectiveness, with the Inquiry model being more dominant in improving science process skills and PBL showing greater influence on the development of critical thinking. Although both are effective, differences in instructional approach and learning focus affect the learning outcomes. The Inquiry model emphasizes exploration and concept discovery through scientific investigation, while PBL emphasizes solving contextual problems that actively engage students cognitively. These findings suggest that integrating the strengths of both models or applying a hybrid approach may lead to more comprehensive learning outcomes in science education at schools.